How Did Sheep Save the Day? The Role of Dry Stone Wall Heritage and Agropastorality in Historical Landscape Preservation. A Case-Study of the Town of Cres Olive Grove - Tanja Kremenić; Goran Andlar; Mauro Varotto (Land, 2021)
The dry stone wall landscape surrounding the town of Cres is a unique cultural landscape; it is one of the largest well-preserved historical olive groves in the Croatian Adriatic, while simultaneously serving as pasture for sheep. Still, there are currently no studies that capture this landscape as a multifunctional whole or which acknowledge its relevance within the current multidisciplinary discussions. The aim of this paper is to clarify past and current circumstances surrounding and affecting it. The study focuses on two main pillars of landscape preservation: (1) dry stone wall structures and (2) agro-pastoral practices; giving an overview of its historical formation and current management and trends. The goal is to establish knowledge that can be used as a foundation for the management of this area and present a good practice example for the preservation of historical landscapes in the Mediterranean region. The research involved combined desk and fieldwork: cartographic data analysis, literature analysis, GIS elaboration, terrestrial and aerial photographs and observations, followed by interviews with local informants. Continuous investing in the production of quality olive oil and the evolution of the landscape into a multifunctional agro-pastoral-touristic space is what enabled its preservation. This multifunctionality can only be matched by a diversity of scientific studies and this study aimed at providing the first step—a foundation for the identification of the values of the Cres landscape, with the scope of better precising further planning and management.